Characterization of the Baobab fruit shells as adsorbtion material - Mustafa, Monawar Munjid; Kabbashi, Nassereldeen Ahmed; Al-Khatib, Ma'an Fahmi Rashid; Alam, Md. Zahangir (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
The Baobab (Adansonia digitata L.) is a large iconic tree indigenous to Africa where it is found in many countries. The Baobab tree has various uses, as it produces food and non-food products such as medicines, fuel, timber and fodder. This research is focused on the characterization of the Baobab fruit shells in terms of lignin (54.08%), cellulose (24.87%) and hemicellulose (21.05%) content, as well as proximate analysis such as ash content (5.17%), moisture content (6.48%), volatile matter (86.73%) and carbon content (1.22%). This assessment will play a vital role in exploring the benefits of utilizing baobab fruit shells in the production of activated carbon as well as set a foundation for future research.